PERBANDINGAN ANALISIS KOLOM DENGAN METODE ANALITIS DAN METODE BEDA HINGGA (KASUS KOLOM DENGAN DIMENSI 300x300 mm2, f’ c = 20 MPa, fy = 400 MPa, As + As ’= 1% Ag) - Mukhlis Islam (Universitas Bengkulu, 2019)
The aim of this research is to study the feasibility and effectiveness of finite difference method utilization as an alternative method for reinforced concrete column analysis and design tool beside analytical method which is already ratified by many design codes. The background of the research is that the finite difference method is relatively easier to apply as calculation tool by using computers. In this research the finite difference method is applied to calculate the magnitude of concrete stress that was discretized by using concrete stress strain relationship equations proposed by Hognestad (1951). The results of the research show that the application of finite difference method to calculate the axial and bending moment capacity of reinforced concrete column by using the aforementioned concrete stress strain relationship provide good results with deviation of 5.61% up to 18.70% compares to analytical method for axial capacity, and 0.65% up to 4.33% deviation for bending moment capacity, both on the conservative side.